ANALISIS KEBERADAAN STREET FURNITURE SEBAGAI CITRA KOTA DI KORIDOR JALAN P.B SUDIRMAN, KOTA DENPASAR - Putu Ayu Mirah Sanjiwani Giri; Ngakan Ketut Acwin Dwijendra; Ida Bagus Gede Wirawibawa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
Corridor P.B Sudirman in Denpasar City has not been fully good in terms of facilities and infrastructure such as the arrangement of street furniture which is one of the supporting elements of public space that reinforces the character and image of city street corridors. Street furniture must be integrated and harmonious with other urban design elements to give a neat and orderly impression on the street corridors. The research method used in this research is qualitative - a case study by presenting primary data and where later the data to be used is obtained from surveys, observations in the field and will be compared with existing theories. There are approximately 6 out of 10 types of street furniture or street furniture analyzed, whereof all these types there are several street furniture that still needs to be fixed and corrected as well as its existence because the existence of street furniture in a road corridor area can later lead to the face or image of the corridor The city, especially in this discussion, is the image of Denpasar City on the PB Sudirman corridor thus creating the image of Denpasar City which is cultured and humane.